2006
DOI: 10.1177/0021998306061305
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behavior of Functionalized Multi-walled Carbon Nanotube Reinforced Epoxy Matrix Composites

Abstract: This article studies the tribological behavior of functionalized multiwalled carbon nanotubes (MWNTs) reinforced epoxy matrix composites. MWNTs reinforced epoxy composites are fabricated by an injection molding process. The effects on the tribological properties of different loading concentrations and different functional groups of MWNTs are investigated by using a linear reciprocal wear tester. As increasing the concentration of MWNTs reduces wear loss, better tribological property was attained on functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Carbon nanotubes (CNTs) have demonstrated a remarkably high potential for mechanical and physical properties because of their structure, size, and topology1–4; this has made them attractive for various applications, especially as nanotube‐reinforced materials in nanocomposites, nanoelectronic devices, and so on 5. Since the first report of the low‐friction properties of CNTs,6 researchers have begun to investigate the tribological behaviors of CNT composites, including CNT/copper,7 CNT/Ni‐P,8, 9 CNT/carbon,10 CNT/polyimide,11 CNT/polytetrafluroethylene,12 CNT/poly(methyl methacrylate),13 and CNT/epoxy nanocomposites 14. It was reported that the composites reinforced by CNTs displayed improved friction and wear properties compared with the pure substrate matrix because of the special effects of CNTs 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have demonstrated a remarkably high potential for mechanical and physical properties because of their structure, size, and topology1–4; this has made them attractive for various applications, especially as nanotube‐reinforced materials in nanocomposites, nanoelectronic devices, and so on 5. Since the first report of the low‐friction properties of CNTs,6 researchers have begun to investigate the tribological behaviors of CNT composites, including CNT/copper,7 CNT/Ni‐P,8, 9 CNT/carbon,10 CNT/polyimide,11 CNT/polytetrafluroethylene,12 CNT/poly(methyl methacrylate),13 and CNT/epoxy nanocomposites 14. It was reported that the composites reinforced by CNTs displayed improved friction and wear properties compared with the pure substrate matrix because of the special effects of CNTs 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of multi‐walled carbon nanotubes (MWNTs) in 1991 by Iijima1 has opened a new era in the field of nanotechnology because of the excellent reinforcing and electrical properties of the MWNTs, arising from their special atomic and electronic structures. Nowadays, MWNTs have many important applications, which include catalysts support,2–4 hydrogen storage,5, 6 reinforced materials,7, 8 nanoelectric devices,9, 10 field emission,11, 12 etc. However, their poor solubility and tendency to aggregate together limits their applications 13–15.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that D band (1365 cm -1 ) in epoxy/MWNT is more intense than the band observed for repoxy which indicates MWNT at 1352 cm -1 (figure 5b). This indicates in epoxy/MWNT, more number of CNTs showed defect sites and change to amorphous carbon than in case of repoxy/MWNT (Sulong et al 2006). Again, increase in peak intensity and a little shift in G-band are found in case of repoxy/ MWNT in comparison to epoxy/MWNT.…”
Section: Raman Characterizationmentioning
confidence: 78%